Hubungan Tingkat Pengetahuan Ibu Tentang ASI dengan Tindakan Pemberian ASI Eksklusif di Puskesmas Tumpaan - Henrico N. Rumopa; Nancy S. Bawiling; Lucyana L. Pongoh (Yayasan Syalom Cipta Sumikolah, 2025)
Breast milk, commonly referred to as ASI (Air Susu Ibu), is the best and only recommended food for infants, as it contains the most complete nutritional composition for their growth and development. Exclusive breastfeeding refers to the practice of feeding infants only breast milk for the first six months of life, without any additional food or drink such as formula milk, fruit juice, honey, tea, plain water, or solid foods like bananas, papayas, milk porridge, biscuits, rice porridge, or soft rice. This study aims to examine the relationship between mothers’ knowledge about breastfeeding and their practice of exclusive breastfeeding at Tumpaan Health Center. The research was conducted from July to August 2023 using a quantitative design with a cross-sectional survey approach and accidental sampling technique. The study was conducted at Tumpaan Health Center with a total sample of 40 mothers with infants. Data were analyzed using the Chi-square test. The results showed a significant relationship between the level of maternal knowledge and the practice of exclusive breastfeeding (p = 0.03 < 0.05). It can be concluded that there is a relationship between maternal knowledge and exclusive breastfeeding at Tumpaan Health Center. Based on these findings, it is recommended that healthcare workers enhance their role in providing health education to the community regarding exclusive breastfeeding and its benefits, as well as coordinate with related institutions to further promote exclusive breastfeeding practices.